Machine Translation 18th China Conference, CCMT 2022, Lhasa, China, August 6-10, 2022, Revised Selected Papers - Xiao, Tong.; Pino, Juan. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book constitutes the refereed proceedings of the 18th China Conference on Machine Translation, CCMT 2022, held in Lhasa, China, during August 6-10, 2022. The 16 full papers were included in this book were carefully reviewed and selected from 73 submissions.
PEACook: Post-Editing Advancement Cookbook -- Hot-start Transfer Learning combined with Approximate Distillation for Mongolian- Chinese Neural Machine Translation -- Review-based Curriculum Learning for Neural Machine Translation -- Multi-Strategy Enhanced Neural Machine Translation for Chinese Minority Language -- Target-side Language Model for Reference-free Machine Translation Evaluation -- Life Is Short, Train It Less: Neural Machine Tibetan-Chinese Translation Based on mRASP and Dataset Enhancement -- Improving the Robustness of Low-Resource Neural Machine Translation with Adversarial Examples -- Dynamic Mask Curriculum Learning for Non-Autoregressive Neural Machine Translation -- Dynamic Fusion Nearest Neighbor Machine Translation via Dempster-Shafer Theory -- A Multi-tasking and Multi-stage Chinese Minority Pre-Trained Language Model -- An improved Multi-task Approach to Pre-trained Model Based MT Quality Estimation -- Optimizing Deep Transformers for Chinese-Thai Low-Resource Translation -- HW-TSC Submission for CCMT 2022 Translation Quality Estimation Task -- Effective Data Augmentation Methods for CCMT 2022 -- NJUNLP's Submission for CCMT 2022 Quality Estimation Task -- ISTIC's Thai-to-Chinese Neural Machine Translation System for CCMT' 2022.
Keywords: Natural language processing (Computer science).; Database management; Computer science; Coding theory; Information theory; Social sciences-Data processing; Natural Language Processing (NLP).; Database Management; Computer Science Logic and Foundations of Programming; Coding and Information Theory; Computer Application in Social and Behavioral Sciences